Myerson, Ida (audio interview #1 of 1) - Myerson, Ida (b. 01/01/1888 - d. unknown)
INTERVIEW DESCRIPTION - No details are available concerning the circumstances of the single one hour interview done with Myerson. TOPICS - family background and history; early life in Russia; immigration to US; housing and living arrangements in Philadelphia; family relationships; education; work history; organizing for Waterproof Garment Workers Union; working conditions and wages in shirtwaist factories; general strikes; fundraising for the shirtwaists Locals; child labor; election as secretary of Shirtwaist Locals; role as assistant to secretary-treasurer of ILGWU; Pauline Newman; Rose Schneiderman; WTUL; ILGWU unemployment insurance fund; and arrests; Note: the audio quality towards the end of this interview is fair;conviction of union officials in alleged murder of manufacturer; downsizing of ILGWU; internal politics, ILGWU; position with Joint Action Committee; development of unemployment insurance fund; work with the Waterproof Garment Workers Union and strike negotiations; Note: the audio quality of this interview is fair; 1974